Copper monatomic carbon dot nano-enzyme with SOD (superoxide dismutase) enzyme activity as well as preparation method and application thereof

By loading copper single atoms on the surface of nitrogen-doped carbon quantum dots, the problem that copper elements cannot be fully loaded in the form of copper single atoms is solved, and efficient and stable copper single atom load is achieved, improving the activity of nanoenzymes and metal utilization rate.

CN119503778AActive Publication Date: 2025-02-25XUCHANG UNIV
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411657236.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-25
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

In the existing copper-doped carbon dot nanoenzymes, copper elements cannot be completely loaded on the carbon dot in the form of copper single atoms, resulting in a decrease in the utilization rate of metal atoms.

Method used

By loading copper single atoms on the surface of nitrogen-doped carbon quantum dots, and coordinate with Cu2+ using the asymmetric C and N sites on the surface of nitrogen-doped carbon quantum dots, uniform loading and stable dispersion of copper single atoms are achieved.

Benefits of technology

The efficient loading and stable existence of copper single atoms is achieved, the activity, stability and metal economy of nanoenzymes are improved, and the scavenging ability of superoxide radicals is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503778A_ABST
    Figure CN119503778A_ABST
Patent Text Reader

Abstract

The invention relates to a copper monatomic carbon dot nano-enzyme with SOD (superoxide dismutase) enzyme activity as well as a preparation method and application thereof. The copper monatomic carbon dot nano-enzyme with the SOD enzyme activity is obtained by loading copper monatomic on the surface of a nitrogen-doped carbon quantum dot, and the copper monatomic is dispersed on the surface of the nitrogen-doped carbon quantum dot in the form of Cu < 2 + >. Various asymmetric C and N sites exist on the surfaces of the nitrogen-doped carbon quantum dots, the existence of N is beneficial to promoting Cu < 2 + > dispersion and reducing Cu < 2 + > agglomeration, stable Cu < 2 + > atomic-scale dispersion is realized through coordination of N and Cu < 2 + >, and the high activity, the stability and the metal economy of the copper monatomic carbon dot nano-enzyme with the SOD enzyme activity are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of nanozyme preparation, and in particular relates to a copper single-atom carbon dot nanozyme with SOD enzyme activity, a preparation method and an application thereof. Background Art

[0002] Oxidative stress damage induced by overexpression of reactive oxygen species (ROS) and reactive nitrogen species (RNS) in organisms is considered to be one of the important causes of many biological diseases. Natural enzymes play a key role in maintaining redox balance in the body and alleviating oxidative stress damage; however, the preparation and purification steps of natural enzymes are complicated, costly, and the storage conditions are harsh. Although natural superoxide dismutase (SOD enzyme) has broad prospects in disease treatment, it is not satisfactory in practical applications due to its instability under non-physiological conditions and susceptibility to proteolytic enzymes. In addition, natural SOD enzymes are usually difficult to cross the cell membrane to remove excess ROS. As a new generation of artificial enzyme mimics, nanozymes have unique enzyme mimic properties and can be used for human health and disease treatment. Antioxidant nanozymes that remove ROS are potential materials for treating inflammatory damage diseases induced by ROS in organisms.

[0003] There are various functional groups on the surface of carbon quantum dots (CDs), including carbonyl, hydroxyl and carboxyl groups, which can realize various enzyme activities based on different enzyme catalytic active sites on the surface. Inspired by the concept of single-atom catalysts, atomically dispersed metal atoms anchored on the carrier can provide the highest atomic utilization, thus providing more efficient active sites for biochemical reactions. Therefore, single-atom nanozymes are constructed by simulating the metal coordination structure of natural metalloenzymes, so that these metal atoms can be used to consume superoxide radicals (O2 ·- Although some single-atom nanozymes have been successfully developed, the common synthesis method of one-pot pyrolysis of metal salts, carbon and nitrogen precursors will embed some metal atoms inside the carbon skeleton, reducing the proportion of catalytic sites on the surface of the nanozyme, resulting in a decrease in the utilization rate of metal atoms.

[0004] The invention patent with application publication number CN118146794A discloses a single-atom copper-doped near-infrared carbon dot and its preparation method and application. The single-atom copper-doped near-infrared carbon dot uses ethylenediaminetetraacetic acid as a carbon source, a copper salt as a copper source, and water as a solvent. The single-atom copper-doped near-infrared carbon dot is obtained by hydrothermal reaction. However, the copper element in the single-atom copper-doped near-infrared carbon dot cannot be completely loaded on the carbon dot in the form of a single copper atom. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a copper single-atom carbon dot nanozyme with SOD enzyme activity to solve the technical problem that the copper element of the copper-doped carbon dot nanozyme cannot be completely loaded on the carbon dot in the form of a copper single atom.

[0006] The second object of the present invention is to provide a copper single-atom carbon dot nanozyme with SOD enzyme activity.

[0007] The third object of the present invention is to provide an application of a copper single-atom carbon dot nanozyme having SOD enzyme activity.

[0008] In order to achieve the above purpose, the technical solution adopted by the present invention is:

[0009] The copper single-atom carbon dot nanozyme with SOD enzyme activity is obtained by loading copper single atoms on the surface of nitrogen-doped carbon quantum dots. 2+ dispersed on the surface of nitrogen-doped carbon quantum dots in the form of.

[0010] Furthermore, the loading amount of the copper single atom accounts for 5-20wt% of the nitrogen-doped carbon quantum dots.

[0011] The preparation method of copper single-atom carbon dot nanozyme with SOD enzyme activity is characterized by comprising the following steps: mixing a nitrogen-doped carbon quantum dot aqueous solution with a copper source and drying the mixture to obtain a powder, and heating the powder with a microwave to obtain the nanozyme after purification.

[0012] Furthermore, the preparation method of the nitrogen-doped carbon quantum dot aqueous solution is: dissolve citric acid in water, then mix it with ethylenediamine to obtain a mixed solution, subject the mixed solution to a hydrothermal reaction, centrifuge to obtain a supernatant, freeze-dry the supernatant to obtain a nitrogen-doped carbon quantum dot powder, and dissolve the nitrogen-doped carbon quantum dot powder in water.

[0013] Furthermore, the power of the microwave heating is 600-800W; and the time of the microwave heating is 0.5-2min.

[0014] Furthermore, the concentration of the nitrogen-doped carbon quantum dot aqueous solution is 1 to 5 mg / mL.

[0015] Furthermore, the temperature of the hydrothermal reaction is 180-200° C., and the time of the hydrothermal reaction is 4-6 hours.

[0016] Furthermore, 10 to 15 mL of water is added to every 1.05 g of the citric acid, and 0.335 to 0.67 mL of ethylenediamine is added to every 1.05 g of the citric acid.

[0017] Furthermore, the copper source is copper chloride; the drying method is freeze drying; and the purification method is: dissolving the powder after microwave heating in water for dialysis purification.

[0018] Application of copper single-atom carbon dot nanozymes with SOD enzyme activity in scavenging superoxide radicals.

[0019] Beneficial effects of the present invention:

[0020] The copper single atom carbon dot nanozyme with SOD enzyme activity of the present invention is Cu 2+ The copper element is uniformly loaded on the surface of nitrogen-doped carbon quantum dots. The copper element on the surface of nitrogen-doped carbon quantum dots exists in the form of single copper atoms and does not contain single copper and copper nanoparticles.

[0021] In the present invention, there are multiple asymmetric C and N sites on the surface of nitrogen-doped carbon quantum dots, and the presence of N is beneficial to promote the Cu 2+ Dispersion, reduction of Cu 2+ Agglomeration, through N and Cu 2+ Coordination to achieve stable Cu 2+ The atomic-level dispersion ensures the high activity, stability and metal economy of the copper single-atom carbon dot nanozyme with SOD enzyme activity of the present invention.

[0022] The present invention realizes the uniform loading of copper single atoms on the surface of nitrogen-doped carbon quantum dots by microwave short-time treatment. Relying on the small size, high dispersity and low biological toxicity of carbon quantum dots, copper single atoms with high activity and high atomic utilization are loaded on the surface of nitrogen-doped carbon quantum dots to realize the oxidation of O2 ·- Efficient removal.

[0023] The catalytic active sites of the copper single-atom carbon dot nanozyme with SOD enzyme activity of the present invention are uniformly exposed on the surface of the nitrogen-doped carbon quantum dots, so that the copper single atom can contact the substrate and further mediate the catalytic reaction. The electron spin resonance spectroscopy (ESR) test technology confirms that the activity mechanism of the copper single-atom carbon dot nanozyme with SOD enzyme activity is consistent with the activity mechanism of natural Cu and Zn-SOD enzymes, and the copper single atom can be used to achieve O2 ·- to clear. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The synthetic route of the copper single-atom carbon dot nanozyme with SOD enzyme activity in Example 1;

[0025] Figure 2 The transmission electron microscope image, average particle size curve and optical image of the copper single-atom carbon dot nanozyme with SOD enzyme activity in Example 4 are shown in Figure 4, wherein a is a transmission electron microscope image, and b is an optical image of the average particle size curve and dispersion in water;

[0026] Figure 3 : Characterization diagram of copper single-atom carbon dot nanozyme with SOD enzyme activity, wherein a is the XRD diagram of the copper single-atom carbon dot nanozyme with SOD enzyme activity in Example 1-4, b is the UV-Vis absorption spectrum of the copper single-atom carbon dot nanozyme with SOD enzyme activity in Example 1-4, c is the PL spectrum of the copper single-atom carbon dot nanozyme with SOD enzyme activity in Example 1-4, d is the XPS fine spectrum of C1s of the copper single-atom carbon dot nanozyme with SOD enzyme activity in Example 4, e is the XPS fine spectrum of N1s of the copper single-atom carbon dot nanozyme with SOD enzyme activity in Example 4, f is the Cu of the copper single-atom carbon dot nanozyme with SOD enzyme activity in Example 4 2p is an XPS fine spectrum, g is an ESR graph of the copper single-atom carbon dot nanozyme with SOD enzyme activity in Example 4, h is an XANES graph of the copper single-atom carbon dot nanozyme with SOD enzyme activity in Example 4, and i is a Fourier transform graph of the CuK edge EXAFS spectra of the copper single-atom carbon dot nanozyme with SOD enzyme activity, copper oxide (CuO), copper phthalocyanine (CuPc), and copper foil (Cu foll) in Example 4;

[0027] Figure 4 Copper single-atom carbon dot nanozymes with SOD enzyme activity to O2 ·- The removal performance of the copper single-atom carbon dot nanozyme with SOD enzyme activity of Example 1-4 at a concentration of 20 μg / mL is ·- b is the clearance spectrum of the copper single-atom carbon dot nanozyme with SOD enzyme activity in Example 4 at a concentration of 80 μg / mL to O2 ·- The clearance spectrum of c is the copper single-atom carbon dot nanozyme with SOD enzyme activity in Example 4 to O2 ·- The cytotoxicity test data of d is the copper single-atom carbon dot nanozyme with SOD enzyme activity in Example 4 and O2 ·- Free radical test spectrum before and after the reaction, e is the copper single atom carbon dot nanozyme with SOD enzyme activity in Example 4 and O2 ·- Cu before and after reaction 2+ Paramagnetic signal spectrum. DETAILED DESCRIPTION

[0028] The present invention will be further described below in conjunction with the embodiments of the present invention and the accompanying drawings.

[0029] Example 1

[0030] The method for preparing the copper single-atom carbon dot nanozyme having SOD enzyme activity of Example 1 comprises the following steps:

[0031] S1: 1.05 g of citric acid was dissolved in 10 mL of deionized water, and then mixed with 0.335 mL of ethylenediamine, and magnetically stirred for 30 min to obtain a mixed solution, which was transferred to a Teflon-lined stainless steel autoclave and reacted at 200 °C for 5 h to obtain a brown-black solution, which was centrifuged at 12000 rpm / min for 10 min to remove large particles in the solution to obtain a supernatant, which was freeze-dried to obtain a nitrogen-doped carbon quantum dot powder, which was dissolved in water to obtain a nitrogen-doped carbon quantum dot aqueous solution.

[0032] S2: 0.5 mg of copper chloride solid and 4.7 mL of nitrogen-doped carbon quantum dot aqueous solution were mixed evenly by magnetic stirring for 2 h, freeze-dried to obtain powder, and the powder was treated in a microwave oven at 800w for 1 min. The powder after microwave was dissolved in water and transferred to a 500Da dialysis bag for dialysis for 24 h to obtain a copper single atom carbon dot (CuSAs-CDs) nanozyme with SOD enzyme activity. The copper single atom loading on the surface of the nitrogen-doped carbon quantum dot in the copper single atom carbon dot nanozyme with SOD enzyme activity in Example 1 was 5wt%. The concentration of the nitrogen-doped carbon quantum dot aqueous solution was 1mg / mL.

[0033] Example 2

[0034] The method for preparing the copper single-atom carbon dot nanozyme having SOD enzyme activity of Example 2 comprises the following steps:

[0035] S1: 1.05 g of citric acid was dissolved in 10 mL of deionized water, and then mixed with 0.335 mL of ethylenediamine, and magnetically stirred for 30 min to obtain a mixed solution, which was transferred to a Teflon-lined stainless steel autoclave and reacted at 200 °C for 5 h to obtain a brown-black solution, which was centrifuged at 12000 rpm / min for 10 min to remove large particles in the solution to obtain a supernatant, which was freeze-dried to obtain a nitrogen-doped carbon quantum dot powder, which was dissolved in water to obtain a nitrogen-doped carbon quantum dot aqueous solution.

[0036] S2: 1 mg of copper chloride solid and 4.7 mL of nitrogen-doped carbon quantum dot aqueous solution were mixed evenly by magnetic stirring for 2 h, freeze-dried to obtain powder, and the powder was treated in an 800 W microwave oven for 1 min. The powder after microwave was dissolved in water and transferred to a 500 Da dialysis bag for dialysis for 24 h to obtain a copper single atom carbon dot nanozyme with SOD enzyme activity. The copper single atom loading on the surface of the nitrogen-doped carbon quantum dot in the copper single atom carbon dot nanozyme with SOD enzyme activity in Example 2 was 10 wt%. The concentration of the nitrogen-doped carbon quantum dot aqueous solution was 1 mg / mL.

[0037] Example 3

[0038] The method for preparing the copper single-atom carbon dot nanozyme having SOD enzyme activity of Example 3 comprises the following steps:

[0039] S1: 1.05 g of citric acid was dissolved in 10 mL of deionized water, and then mixed with 0.335 mL of ethylenediamine, and magnetically stirred for 30 min to obtain a mixed solution, which was transferred to a Teflon-lined stainless steel autoclave and reacted at 200 °C for 5 h to obtain a brown-black solution, which was centrifuged at 12000 rpm / min for 10 min to remove large particles in the solution to obtain a supernatant, which was freeze-dried to obtain a nitrogen-doped carbon quantum dot powder, which was dissolved in water to obtain a nitrogen-doped carbon quantum dot aqueous solution.

[0040] S2: 1.5 mg of copper chloride solid and 4.7 mL of nitrogen-doped carbon quantum dot aqueous solution were mixed evenly by magnetic stirring for 2 h, freeze-dried to obtain powder, and the powder was treated in an 800 W microwave oven for 1 min. The powder after microwave was dissolved in water and transferred to a 500 Da dialysis bag for dialysis for 24 h to obtain a copper single atom carbon dot nanozyme with SOD enzyme activity. The copper single atom loading on the surface of the nitrogen-doped carbon quantum dot in the copper single atom carbon dot nanozyme with SOD enzyme activity in Example 3 was 15 wt%. The concentration of the nitrogen-doped carbon quantum dot aqueous solution was 1 mg / mL.

[0041] Example 4

[0042] The method for preparing the copper single-atom carbon dot nanozyme having SOD enzyme activity of Example 4 comprises the following steps:

[0043] S1: 1.05 g of citric acid was dissolved in 10 mL of deionized water, and then mixed with 0.335 mL of ethylenediamine, and magnetically stirred for 30 min to obtain a mixed solution, which was transferred to a Teflon-lined stainless steel autoclave and reacted at 200 °C for 5 h to obtain a brown-black solution, which was centrifuged at 12000 rpm / min for 10 min to remove large particles in the solution to obtain a supernatant, which was freeze-dried to obtain a nitrogen-doped carbon quantum dot powder, which was dissolved in water to obtain a nitrogen-doped carbon quantum dot aqueous solution.

[0044] S2: 2 mg of copper chloride solid and 4.7 mL of nitrogen-doped carbon quantum dot aqueous solution were mixed evenly by magnetic stirring for 2 h, freeze-dried to obtain powder, and the powder was treated in an 800 W microwave oven for 1 min. The powder after microwave was dissolved in water and transferred to a 500 Da dialysis bag for dialysis for 24 h to obtain a copper single atom carbon dot nanozyme with SOD enzyme activity. The copper single atom loading on the surface of the nitrogen-doped carbon quantum dot in the copper single atom carbon dot nanozyme with SOD enzyme activity in Example 4 was 20 wt%. The concentration of the nitrogen-doped carbon quantum dot aqueous solution was 1 mg / mL.

[0045] Example 5

[0046] The method for preparing the copper single-atom carbon dot nanozyme having SOD enzyme activity of Example 5 comprises the following steps:

[0047] S1: 1.05 g of citric acid was dissolved in 13 mL of deionized water, and then mixed with 0.5 mL of ethylenediamine. The mixed solution was obtained after magnetic stirring for 30 min. The mixed solution was transferred to a Teflon-lined stainless steel autoclave and reacted at 180°C for 6 h to obtain a brown-black solution. The brown-black solution was centrifuged at 12000 rpm / min for 10 min to remove large particles in the solution to obtain a supernatant. The supernatant was freeze-dried to obtain nitrogen-doped carbon quantum dot powder. The nitrogen-doped carbon quantum dot powder was dissolved in water to obtain a nitrogen-doped carbon quantum dot aqueous solution.

[0048] S2: 2 mg of copper chloride solid and 4.7 mL of nitrogen-doped carbon quantum dot aqueous solution were mixed evenly by magnetic stirring for 2 h, freeze-dried to obtain powder, and the powder was treated in a 600 W microwave oven for 2 min. The powder after microwave was dissolved in water and transferred to a 500 Da dialysis bag for dialysis for 24 h to obtain a copper single atom carbon dot nanozyme with SOD enzyme activity. The copper single atom carbon dot nanozyme with SOD enzyme activity in Example 5 has a loading amount of 6.7 wt % on the surface of the nitrogen-doped carbon quantum dot. The concentration of the nitrogen-doped carbon quantum dot aqueous solution is 3 mg / mL.

[0049] Example 6

[0050] The method for preparing the copper single-atom carbon dot nanozyme having SOD enzyme activity of Example 6 comprises the following steps:

[0051] S1: 1.05 g of citric acid was dissolved in 15 mL of deionized water, and then mixed with 0.67 mL of ethylenediamine, and magnetically stirred for 30 min to obtain a mixed solution, which was transferred to a Teflon-lined stainless steel autoclave and reacted at 190°C for 6 h to obtain a brown-black solution, which was centrifuged at 12000 rpm / min for 10 min to remove large particles in the solution to obtain a supernatant, and the supernatant was freeze-dried to obtain a nitrogen-doped carbon quantum dot powder, which was dissolved in water to obtain a nitrogen-doped carbon quantum dot aqueous solution.

[0052] S2: 2.5 mg of copper chloride solid and 4.7 mL of nitrogen-doped carbon quantum dot aqueous solution were mixed evenly by magnetic stirring for 2 h, freeze-dried to obtain powder, and the powder was treated in a 700 W microwave oven for 0.5 min. The powder after microwave was dissolved in water and transferred to a 500 Da dialysis bag for dialysis for 24 h to obtain a copper single atom carbon dot nanozyme with SOD enzyme activity. The copper single atom loading on the surface of the nitrogen-doped carbon quantum dot in the copper single atom carbon dot nanozyme with SOD enzyme activity of Example 6 is 5 wt%. The concentration of the nitrogen-doped carbon quantum dot aqueous solution is 5 mg / mL.

[0053] from Figure 2 a and Figure 2 b It can be seen that the average size of the copper single-atom carbon dot nanozymes with SOD enzyme activity is between 4 and 5 nm. Figure 3 a It can be seen that with the increase of copper element loading, the XRD spectrum does not show the characteristic diffraction peak of copper element. Figure 3 b It can be seen that with the increase of copper element loading, the characteristic absorption peak of copper nanoparticles does not appear in the UV-Vis absorption spectrum. Figure 3 a and Figure 3 b shows that the copper element is not loaded on the surface of nitrogen-doped carbon quantum dots in the form of a single substance or nanoparticles, but in the form of copper single atoms. Figure 3 As can be seen in c, with the increase of copper single atom loading, the fluorescence intensity of copper single atom carbon dot nanozyme with SOD enzyme activity decreases, indicating that copper single atoms have been loaded on the surface of nitrogen-doped carbon quantum dots. Figure 3 f- Figure 3 It can be seen that the copper single atom is Cu 2+ The Cu 2+ Coordinated with nitrogen.

[0054] The superoxide dismutase-like activity of the copper single-atom carbon dot nanozymes with SOD enzyme activity of Examples 1-4 was evaluated using the nitroblue tetrazolium (NBT) method at the same concentration. The results are as follows: Figure 4 As shown in a and 4b, with the increase of copper single atom loading, the superoxide dismutase-like activity of the copper single atom carbon dot nanozyme with SOD enzyme activity gradually increased. The copper single atom carbon dot nanozyme with SOD enzyme activity of Examples 1-4 at a concentration of 20 μg / mL was ·- The clearance rates are shown in Table 1. The copper single-atom carbon dot nanozymes with SOD enzyme activity of Examples 1-4 were effective in removing O2 at a concentration of 50 μg / mL. ·- The clearance rates are shown in Table 2. Figure 4 c It can be seen that when the concentration of copper single-atom carbon dot nanozymes with SOD enzyme activity is increased to 80 μg / mL, it still has low toxicity to L929 cells. Figure 4 d and 4e, it can be seen that the copper single-atom carbon dot nanozyme O2 with SOD enzyme activity ·- After the reaction, O2 can be effectively removed ·- Cu on the surface of copper single-atom carbon dot nanozyme with SOD enzyme activity 2+ The paramagnetic signal of ·- In the process, the copper single-atom carbon dot nanozyme with SOD enzyme activity uses the surface copper single atom as the active center to achieve O2 ·- of removal. Figure 4 Blank in b is ESR detection of O2 ·- In the removal experiment, when the copper single-atom carbon dot nanozyme with SOD enzyme activity was not added, O2 ·- The product of the addition of BMPO to the capture agent (BMPO-O2 ·- ) corresponds to the ESR signal; Figure 4 Blank in d is ESR detection of O2 ·- In the removal experiment, when the copper single-atom carbon dot nanozyme with SOD enzyme activity was not added, O2 ·- The product of the addition of BMPO to the capture agent (BMPO-O2 ·- ) corresponds to the ESR signal; Figure 4 Blank in e is the copper single-atom carbon dot nanozyme with SOD enzyme activity and O2 ·- Before the reaction, the copper ions in the copper single-atom carbon dot nanozyme with SOD enzyme activity were detected by ESR to obtain the signal.

[0055] Table 1 Effect of copper single-atom carbon dot nanozymes with SOD enzyme activity on O2 at a concentration of 20 μg / mL ·- The clearance rate

[0056]

[0057] Table 2 Effect of copper single-atom carbon dot nanozymes with SOD enzyme activity on O2 at a concentration of 50 μg / mL ·- The clearance rate

[0058]

[0059] It can be seen from Table 1 and Table 2 that the copper single-atom carbon dot nanozyme with SOD enzyme activity of the present invention has an activity against O2 ·- The removal rate of CDs to O2 ·- When the concentration of copper single-atom carbon dot nanozymes with SOD enzyme activity increases, the removal rate of O2 ·-The removal rate of O2 also increases with the increase of the copper single atom loading on the surface of nitrogen-doped carbon quantum dots. ·- The clearance rate also increased.

Claims

1. A copper single-atom carbon dot nanozyme with SOD enzyme activity, characterized in that: The Cu single atom is obtained by loading Cu single atoms on the surface of nitrogen-doped carbon quantum dots. 2+ dispersed on the surface of nitrogen-doped carbon quantum dots in the form of.

2. The copper single-atom carbon dot nanozyme with SOD enzyme activity according to claim 1, characterized in that: The loading amount of the copper single atom accounts for 5-20 wt % of the nitrogen-doped carbon quantum dots.

3. The method for preparing the copper single-atom carbon dot nanozyme with SOD enzyme activity according to claim 1, characterized in that: The method comprises the following steps: mixing a nitrogen-doped carbon quantum dot aqueous solution with a copper source and drying the mixture to obtain powder; and heating the powder with a microwave to obtain the powder after purification.

4. The method for preparing the copper single-atom carbon dot nanozyme with SOD enzyme activity according to claim 3, characterized in that: The preparation method of the nitrogen-doped carbon quantum dot aqueous solution is as follows: citric acid is dissolved in water, and then mixed with ethylenediamine to obtain a mixed solution, the mixed solution is subjected to a hydrothermal reaction, and a supernatant is obtained after centrifugation, and the supernatant is freeze-dried to obtain a nitrogen-doped carbon quantum dot powder, and the nitrogen-doped carbon quantum dot powder is dissolved in water.

5. The method for preparing the copper single-atom carbon dot nanozyme with SOD enzyme activity according to claim 3, characterized in that: The power of the microwave heating is 600-800W; the time of the microwave heating is 0.5-2min.

6. The method for preparing the copper single-atom carbon dot nanozyme with SOD enzyme activity according to claim 3, characterized in that: The concentration of the nitrogen-doped carbon quantum dot aqueous solution is 1-5 mg / mL.

7. The method for preparing the copper single-atom carbon dot nanozyme with SOD enzyme activity according to claim 4, characterized in that: The temperature of the hydrothermal reaction is 180-200° C., and the time of the hydrothermal reaction is 4-6 hours.

8. The method for preparing the copper single-atom carbon dot nanozyme with SOD enzyme activity according to claim 4, characterized in that: For every 1.05 g of the citric acid, 10 to 15 mL of water is added, and for every 1.05 g of the citric acid, 0.335 to 0.67 mL of ethylenediamine is added.

9. The method for preparing the copper single-atom carbon dot nanozyme with SOD enzyme activity according to claim 3, characterized in that: The copper source is copper chloride; the drying method is freeze drying; and the purification method is: dissolving the powder heated by microwave in water for dialysis purification.

10. Use of the copper single-atom carbon dot nanozyme with SOD enzyme activity as claimed in claim 1 in scavenging superoxide free radicals.

Citation Information

Patent Citations

  • Preparation method and application of carbon-based nano hybrid material

    CN107652970A

  • Targeting copper-doped carbon dots and preparing method and application thereof

    CN110151995A

  • Synthesis method and application of nitrogen-doped carbon fold cage supported copper monatomic catalyst

    CN115228498A

  • Carbon-nitrogen material loaded monatomic copper catalyst as well as synthesis method and application thereof

    CN115282997A

  • Monatomic transition metal doped carbon nitride quantum dot as well as chemical cutting preparation method and application thereof in water phase

    CN115959635A